Comparison of Direct Iliofemoral Stenting Following AngioJet Rheolytic Thrombectomy vs Staged Stenting After AngioJet Rheolytic Thrombectomy Plus Catheter-Directed Thrombolysis in Patients With Acute Deep Vein Thrombosis. (February 2018) - Liu, Guang; Qin, Jinbao; Cui, Chaoyi; Ye, Kaichuang; Shi, Huihua; Liu, Xiaobing; Yin, Minyi; Huang, Xintian; Lu, Min; Jiang, Mier; Li, Weimin; Lu, Xinwu
Purpose: To compare the treatment outcomes in patients with acute proximal deep vein thrombosis (DVT) and iliofemoral stenosis who underwent either direct stenting after AngioJet rheolytic thrombectomy or staged stenting after AngioJet thrombectomy plus catheter-directed thrombolysis with urokinase.Methods: From June 2014 to February 2016, 91 DVT patients underwent 2 treatments for duplex-verified iliofemoral stenosis: direct stenting (n = 46; mean age 54.8 years; 32 men) or staged stenting (n = 45; mean age 56.5 years; 27 men). The degree of patency after thrombectomy or thrombolysis was evaluated using the Venous Registry Index (VRI), while the risk of postthrombotic syndrome (PTS) was evaluated according to the Villalta scale. Patients were followed with periodic duplex ultrasound scans up to 1 year.Results: The technical success rates were 100% in both groups; there was no 30-day mortality. Immediate (24-hour) clinical improvement was achieved in 42 (91%) of 46 direct group patients vs 33 (73%) of 45 staged group patients (p<0.001). A significant reduction (p<0.001) in the length of hospital stay was noted in the direct group (4.59±0.91) compared with that in the staged group (5.8±1.6). The stents used in the direct group were longer but with similar diameter compared with the staged group. The thrombolysis rates were 81.50%±5.76% in the direct group and 85.67%±3.84% in the staged group (p<0.001). The VRIs declined (improved) significantly in both groups (11.68±1.92 to 3.21±1.44 in the direct group and 12.17±2.29 to 2.36±1.19 in the staged group, both p<0.001). The Villalta scores were significantly better in the staged group (p<0.001). Recurrent DVT occurred in 2 patients in the direct group. The primary patency rates at 1 year were 93.5% in the direct group and 97.8% in the staged group (p=0.323).Conclusion: Both direct and staged stenting are effective treatment modalities for patients with acute proximal DVT. Compared with staged stenting, direct stenting provides similar treatment success and a significant reduction in the length of hospital stay; however, it has lower thrombolysis efficacy, and the risk of PTS at 1 year is greater with direct stenting.